Determination of Some Serum Biochemical Parameters of Aksaray Malakli Breed of Turkish Shepherd Dog - Olga Büyükleblebici (Turkish Journal of Agriculture: Food Science and Technology)
Aksaray Malakli Shepherd Dog is a native Anatolian race which is raised in Aksaray and it is marked recently. This study is prepared to reveal significative biochemical properties of Aksaray Malakli Dog. Blood samples were collected from 20 Malakli dogs which are raised in various animal shelters in Aksaray region. Biochemical parameters; serum total protein, albumin, globulin, blood urea nitrogen, creatinine, glucose, total cholesterol, triglyceride, calcium, phosphor, iron, ferritin, and ALP, AST, ALT, creatine enzyme activities were measured calorimetrically. Obtained results were 6.25 g/dL, 3.62 g/dL, 2.63 g/dL, 16.53 mg/dL, 0.88 mg/dL, 91.10 g/dL, 186.85 mg/dL, 47.65 mg/dL, 9.53 mg/dL, 4.36 mg/dL, 112.45 µg/dL, 0.51 ng/dL respectively. and enzyme levels were 42.50 IU/L, 31.90 IU/L, 43.30 IU/L, 166.4 IU/L, respectively. Serum Paraoxonase 1 and hepcidine levels were measured with ELISA kits manually. Obtained results were 33.0 ng/ml and 23.55 ng/ml respectively. With this study, we determined some serum biochemical parameters of Malakli dog and we tried to find out the differences between the other Anadolu Çoban dogs. Obtained results may be useful for the next studies about morbidity-health status of these dogs.